Sistem Analisa Sentiment Bakal Calon Presiden 2024 Menggunakan Metode NLP Berbasis Web - Abdul Mukti; Anggun Dwi Hadiyanti; Airlangga Nurlaela; Jeremy Panjaitan (LPPM Politeknik Saint Paul Sorong, 2023)
The spread of forecasts for presidential candidates in digital media, especially articles, has created public interest in the popularity, politics and performance of the presidential candidate, which has the effect of leading public opinion to positive or negative sides depending on people's assessments, arguments and information conveyed. In increasing sources of accurate information on the election of presidential candidates, an information system will be built that will assist the public in objectively selecting presidential candidates. The word processing method will be processed and managed by Natural Language Processing (NLP) using the Naïve Baiyes Classifier Algorithm by comparing the KBBI (Big Indonesian Dictionary) vocabulary so that conclusions can be drawn about people's emotions (positive, negative and even neutral) and will present information in the form of charts , trends and content.